Diving into commercial cellulase formulations for circular polyester/cotton separation through targeted depolymerization of cotton - Egan, Jeannie; Barta, Michael; Pointner, Patrick; Herbinger, Birgit; Rudolf-Scholik, Judith; Gruenfelder, Agnes; Lilek, David; Rosenau, Thomas; Guebitz, Georg M.; Schimper, Christian B. (Frontiers in Bioengineering and Biotechnology, 2025)
The rapid growth of the textile industry, driven by fast fashion trends, has significantly increased textile waste, particularly blends of polyester (PET) and cotton fibers, and efficient recycling of blended textiles requires effective fiber separation methods, yet current strategies face substantial limitations. This study investigates the performance of commercially available cellulase formulations for enzymatic depolymerization of cotton and suggests an optimized activity pattern for novel reactor systems for recycling of PET/cotton blends. Thirty-five cellulase formulations intended for biopolishing, stonewashing, or biomass degradation were extensively characterized through biochemical assays (protein quantification, reducing sugar content, SDS-PAGE, and enzyme-specific activity assays). The formulations were further categorized according to their physical state, optimal pH and temperature class, and use case (biopolishing, stonewashing, and degradation), and trends were observed between the categories. Ten formulations were selected for further practical evaluation in a controlled reactor system to determine cotton removal efficacy from a blended PET/cotton fabric based on cotton weight loss. Enzyme activity assays did not correlate directly with reactor performance, suggesting that conventional cellulase assays may inadequately predict real-world separation efficiency. Protein efficiency was introduced as a critical metric for evaluating enzyme efficacy and economic viability. Here this variable was defined as a specific activity, relating the fiber separation efficiency in the reactor to the protein content of the formulation to indicate how effective the proteins were at separation. Formulations exhibiting balanced high performance in both weight loss and protein efficiency predominantly contained high proportions of endoglucanase activity, supported by moderate cellobiohydrolase and minor beta-glucosidase activities.